A Comprehensive Measurement for Sustainability Reporting Quality: Principles-Based Approach - Paulina Permatasari; Juniati Gunawan; Magdi El-Bannany (Universitas Pasundan, 2020)
This study presents a comprehensive approach to measure sustainability reporting quality (SRQ) and examines levels of SRQ. It was then used to measure SRQ in Indonesia. Based on reporting guidelines, the new comprehensive measurement for SRQ was developed by not only evaluating the extent of disclosures, but also by examining the quality. The content analysis was conducted to measure the level of SRQ using this comprehensive measurement. The samples are from stand-alone sustainability reports of companies. The results indicate that the overall score for SRQ was moderate. The score was derived using five aspects: the extent of quantitative reporting, the extent of qualitative reporting, the content of the report, the quality of the report, and sustainability reporting accordance. This proposed comprehensive SRQ measurement was used to examine the quantitative and qualitative aspects. This measurement will help academicians to examine the quality of reports and provide more credible assessments that can be used by practitioners to analyze the content of the report. Applying the SRQ measure to Indonesian companies empirically enriches the existing literature and creates a new platform for future studies.Â